Implementasi Etika Bisnis Islam Pelaku Usaha Mikro Kecil dan Menengah (UMKM) di Kecamatan Sibulue - Mutiara, Mutiara; Marzuki, Sitti Nikmah; Amir, Muhammad Fakhri (AL-Muqayyad, 2024)
The majority of MSMEs in Sibulue District are Muslim and many are interested in culinary businesses, which can trigger competition among business actors. Islamic business ethics are needed to create healthy competition in carrying out business activities. The aim of this research is to determine the application of Islamic business ethics principles and business patterns to culinary MSMEs in Sibulue District. This research is field research using qualitative methods, namely research based on non-numerical data, such as words and pictures. The data sources for this research are primary data and secondary data. In this research, Miles & Huberman's interactive model data analysis is directed at reducing data, presenting data, and verifying data to draw conclusions. The results of this research indicate that several business actors in Sibulue District have implemented the principles of business ethics. There is no evidence of irregularities committed by business actors in facing competition or in serving consumers. Likewise, in implementing business patterns, culinary business actors in Sibulue District do not apply business patterns that can harm other parties.